REDOUBLEMENT ET ESTIME DE SOI CHEZ DES ÉLÈVES BURKINABÈ DU PRIMAIRE - Leopold, Badolo B. (European Scientific Journal, ESJ, 2012)
Debates about the effects of repetition of self-esteem of learners are not unanimous in the authors. This article aims to contribute to this debate. To do this, a probability sample of 120 subjects, CM2 level, was questioned. It consists of fifty four (54) repeaters and sixty six (66) unlined, with an estimated average age 12 years ± 8 months. The results show that there is no necessary link between direct and repetition and self-esteem. They invite us to consider the relationship between these two variables are modulated by the intervention of other variables.